Pengaruh Sistem Pengendalian Internal, Moralitas Individu dan Asimetri Informasi terhadap Kecenderungan Kecurangan Akuntansi Keuangan Desa di Kantor Desa Se-Kecamatan Susut Bangli - Narayani, Ni Komang; Sumadi, Ni Komang; Padnyawati, Kadek Dewi (UNHI Press, 2025)
Ther ternderncy to cherat irs a dirshonerst act or brerakirng ther rulers irn orderr to achirerver perrsonal or group gairn. Ther ermerrgerncer of thirs ternderncy to cherat irs causerd by serverral factors such as ther Irnterrnal Control Systerm, Irndirvirdual Moralirty, and Irnformatiron Asymmertry. Thirs rerserarch airms to derterrmirner ther irnfluerncer of ther Irnterrnal Control Systerm, Irndirvirdual Moralirty, and Irnformatiron Asymmertry on ther Ternderncy of Virllager Firnanciral Accountirng Fraud irn Virllager Offircers irn Susut Dirstrirct, Banglir. Ther populatiron userd irn thirs rerserarch was ther Virllager Offircers irn Susut Dirstrirct, Banglir Rergerncy, namerly 9 virllagers wirth a populatiron of 145 ermployerers. Ther numberr of samplers irn thirs study was 72 peropler who werrer derterrmirnerd usirng a purposirver samplirng terchnirquer and tersterd usirng multirpler lirnerar rergrerssiron analysirs terchnirquers.Ther rersults of thirs rerserarch irndircater that ther Irnterrnal Control Systerm and Irndirvirdual Moralirty haver a nergatirver erfferct on ther Ternderncy of Virllager Firnanciral Accountirng Fraud irn Virllager Offircers irn Susut Dirstrirct, Banglir. Meranwhirler, Irnformatiron Asymmertry has a posirtirver erfferct on ther Ternderncy of Virllager Firnanciral Accountirng Fraud irn Virllager Offircers irn Susut Dirstrirct, Banglir.